2020
DOI: 10.1111/dth.13944
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal injection of incobotulinumtoxinA for face lifting

Abstract: Intradermal injection of botulinumtoxinA (BoNT/A) has been used off-label by many clinicians for the purpose of face-lifting effect. Some studies on AbobotulinumtoxinA (AboA) demonstrated clinical efficacy on face-lifting effect when comparing to normal saline solution (NSS). So far, there is no split-face comparison study on facelifting effect of IncobotulinumtoxinA (IncoA). The objective of this study was to compare the face-lifting effect of IncoA intradermal injection and NSS. Twenty-two subjects were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…24 Indeed, when injections were performed along the hair and jawlines, this somewhat created face-lift–like vectors, which probably accounts for some semblance of the face-lifting effect observed. 11–13,15 Finally, while the dilution, concentration, type, and total dose of botulinum toxin used were all highly varied in this study, analysis of results suggest that an average of 20 to 30 BU (or equivalent) would produce a face-lifting effect, provided the injection patterns were designed to recreate face-lift vectors, sort of, as mentioned. It does seem, however, that injecting with 30-G needles resulted unanimously in procedure-related pain, 9,15 whereas studies that utilized 32-G needles only reported minimal bruising in 13.8% of patients, 13 so this may be worth bearing in mind.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…24 Indeed, when injections were performed along the hair and jawlines, this somewhat created face-lift–like vectors, which probably accounts for some semblance of the face-lifting effect observed. 11–13,15 Finally, while the dilution, concentration, type, and total dose of botulinum toxin used were all highly varied in this study, analysis of results suggest that an average of 20 to 30 BU (or equivalent) would produce a face-lifting effect, provided the injection patterns were designed to recreate face-lift vectors, sort of, as mentioned. It does seem, however, that injecting with 30-G needles resulted unanimously in procedure-related pain, 9,15 whereas studies that utilized 32-G needles only reported minimal bruising in 13.8% of patients, 13 so this may be worth bearing in mind.…”
Section: Discussionmentioning
confidence: 82%
“…The immediacy of a face-lifting effect was investigated through direct assessment by the blinded treating physician, which was seen 50%, 11 55.2%, 13 and 63.6% 12 of the time when DYS, DYS, and XEO were used, respectively, in 3 separate studies; this represents an overall efficacy of only 10.8% (40/372) in achieving an immediate face-lifting effect. It was also shown objectively through three-dimensional imaging analysis that overall, such face-lifting effects from micro-btx, if any, can last for up to 3 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations